Are the goals of therapy achievable in patients with rheumatoid arthritis receiving upadacitinib in real clinical practice? - V. N. Amirjanova; A. E. Karateev; E. Yu. Pogozheva; E. S. Filatova; R. R. Samigullina; V. I. Mazurov; O. N. Anoshenkova; N. A. Lapkina; A. A. Baranov; T. Yu. Grineva; A. M. Lila; E. L. Nasonov (Научно-практическая ревматология, 2022)
The aim of the study was to evaluate the effectiveness of UPA in RA patients in real clinical practice after 3 and 6 months of therapy.Material and methods. The study included 63 RA patients with high activity of the disease. Activity was assessed according to the DAS28 (ESR), DAS28 (CR P), SDAI, CDAI; functional ability to HAQ; quality of life to the EQ-5D; disease activity according to the patient’s RAPID-3 index; the level of depression and anxiety to the HADS scale. The effectiveness of therapy was evaluated after 3 (n=45) and 6 (n=31) months of UPA therapy.Results. Remission or low activity of the disease by 3 months of therapy was achieved by most patients: remission of 69.8% of patients, low activity of the disease – 16.3% of patients. Moderate or high activity persisted in 13.9% of patients. By the 6th month of UPA therapy, the number of remissions reached 90% , low activity – 3.3%, moderate activity persisted in 6.7% of patients, high activity of the disease was not in any patient. 20% improvement in function was achieved in 71.8% of patients by the 3rd month of therapy and in 77.8% – by the 6th month of treatment; the difference in average HAQ values by the 3rd month of therapy was 0.38 points, by the 6th month – 0.58 points. After 3 months of follow-up, 31.1% of patients continued taking GC, by 6 months – 24.2%. The dose of GC was reduced from an average of 7.23 mg/d to 5.6 mg/d. The percentage of patients requiring NSAIDs decreased from 95.2% to 35.6% and 33.3%, respectively. DMARDs continued to be received by 75.6% of patients by 3 months and 69.7% by 6 months of follow-up.Conclusion. Achieving remission or low activity of the disease in patients with RA receiving UPA in real clinical practice is possible in most patients. A rapid decrease in inflammatory activity is accompanied by a significant improvement in the functional state and quality of life of patients. UPA therapy reduces the need for the use of NSAIDs and reduces the dose of GC in a third of patients.